Chemical shift separation with controlled aliasing for hyperpolarized 13C metabolic imaging. Issue 4 (8th October 2014) - Shin, Peter J.; Larson, Peder E.Z.; Uecker, Martin; Reed, Galen D.; Kerr, Adam B.; Tropp, James; Ohliger, Michael A.; Nelson, Sarah J.; Pauly, John M.; Lustig, Michael; Vigneron, Daniel B.
<x xml:space="preserve">Abstract</x> Purpose A chemical shift separation technique for hyperpolarized 13C metabolic imaging with high spatial and temporal resolution was developed. Specifically, a fast three‐dimensional pulse sequence and a reconstruction method were implemented to acquire signals from multiple 13C species simultaneously with subsequent separation into individual images. Theory and Methods A stack of flyback echo‐planar imaging readouts and a set of multiband excitation radiofrequency pulses were designed to spatially modulate aliasing patterns of the acquired metabolite images, which translated the chemical shift separation problem into parallel imaging reconstruction problem. An eight‐channel coil array was used for data acquisition and a parallel imaging method based on nonlinear inversion was developed to separate the aliased images. Results Simultaneous acquisitions of pyruvate and lactate in a phantom study and in vivo rat experiments were performed. The results demonstrated successful separation of the metabolite distributions into individual images having high spatial resolution. Conclusion This method demonstrated the ability to provide accelerated metabolite imaging in hyperpolarized 13C MR using multichannel coils, tailored readout, and specialized RF pulses. Magn Reson Med 74:978–989, 2015. © 2014 Wiley Periodicals, Inc.